Fernando Pessoa: Portugal in His Heart - B. F. Martynov (Ибероамериканские тетради)
The name of Fernando Pessoa (1888–1935), who is a great Portuguese poet and political journalist, unfortunately is not well known to the common Russian reader. In Portugal he became famous only after his premature death. Besides his unquestionable talent, the poet was well known because of his «heteronyms», i.e. imaginary authors (he had more than 42 of them). Along with that, every one of his «heteronyms» had his own biography and literary style. The majority of those who study the creative work of Fernando Pessoa (one of the most prominent of them is the British literary critic R. Zenith), believe, dealing with his «phenomenon», that the peculiarities of this man in many aspects were caused by the specific features of his character, love for his home country and its language, and by his faith in the «Sebastianist» idea (16th century). Deeply submerged in his inner world, the poet frequently did not separate his fantasies from the reality, showing along with that his surprising proper feeling of that reality and the unique capacity to foresee it. As a political journalist, Pessoa is interesting to study due to his views on the history of Portugal and the future of Europe. His views have drifted from the early republicanism to the «scientific monarchism» in the adult times, and testified that the poet never stopped in his studies of the outer world, suggesting his own, sometimes rather original ways of its understanding. At the same time, Pessoa’s views resonate to a certain degree with those of Russian philosophers A. Losev and M. Bakhtin. The «Sebastianist» myth and the project of the «Fifth Empire» were interlaced in the Pessoa’s philosophic heritage with the concept of Portuguese national identity. Without them he didn’t see any perspectives for the future development of his country. Utopia in his works never denied the reality, rather it creatively developed and complemented the latter. Partly, utopia might reflect his response to the reactionary trends within Portugal as well as in Europe as a whole in the 1930s. The transfer of his ashes to the famous Jerónimos Monastery in 1985, where the remains of Vasco da Gama, Camões and the King Sebastian also lay, symbolized the recognition of Pessoa as a Great Portuguese poet.